Antimicrobial activity of Fagoniaindica from Thal Desert, Punjab, Pakistan - Rehana Kouser; Rahmatullah Qureshi (International Journal of Phytomedicine, 2013)
Fagoniaindicais a member of Zygophyllaceae family. The plant is used in indigenous medicine to treatvarious ailmentssuch as tumors, abscesses, wounds, scrofulous glands and other swellings of neck. The present study was designed to evaluate antimicrobial activity of this plant. For this purpose, polarity based extraction of the powdered sampleswere carried out with n-hexane, chloroform, acetone, ethyl acetate, butanol, ethanol and methanol. The extracts were tested on fungal pathogens viz., A.niger, F.oxysporum, A.fumigatus, C.albicansand N.sitophillaand bacterial strains i.e., S. aureus, S.epidermidis, E. coli, K.pneumoniae, P.aeruginosa, S.typi, L.bulgaricus and M.luteus. All the extracts isolated from F.indicahave demonstrated pronounced antibacterial and antifungal activity.Maximum activities were shown by acetone and ethyl acetate extracts which exhibited activity against all the tested bacterial strains.Maximum antifungal activity was expressed by ethyl acetate extract which inhibited all fungal pathoges.The present study supports the use of this plant in traditional medicines as an effective drug used to treat various skin diseases.